Simulation of combustion processes of liquid fuels method the level set - Askarova А.; Bolegenova, S.; Bolegenova, S.; Maximov, V.; Ospanova, Sh.; Beketayeva, M.; Nugymanova, A.; Baizhauma, Zh. (Recent Contributions to Physics, 2017)
Numerical research of burning of liquid fuels is a complex challenge of thermo physics as demands the accounting of a large number of the difficult interconnected processes and the phenomena. Therefore, computing experiment becomes more and more important element of research of processes of burning and design of various devices using burning process. In this article we propose the mathematical model and the main equations describing process of burning of liquid fuels at high turbulence is stated. Research of processes of disintegration and dispersion depending on pressure and an initial lot of injection in the combustion chamber of liquid fuel is conducted: heptane. A study of the distribution of droplets of heptane the radius in the combustion chamber. Even with the same values of the distribution radius have different description in the combustion chamber. In the basic model of the combustion chamber the minimum value of the radius is 5 μm, and the maximum value is 50 microns. However, particles along the height of the combustion chamber are distributed in different ways. The obtained curves of temperature distribution in different points in time drops of heptane in the combustion chamber. The results obtained using the model stochast. On the lower part of the combustion chamber are large particles. t =0,98 ms and their temperature equal to 400K. In another moment of time the particles are apart and moving up the height of the combustion chamber. The temperature of the particles is equal to 500 K at time t = 1,49 ms.